(untitled) (Integral Research, 2025)
This study examines the existence of Kiswahili variations in international communication. It is anchored on two theories: the Wave Theory, which explains the origin and dispersion of language as resembling water waves with contact effects, and Howard Giles’ Communication Accommodation Theory, which considers accommodation strategies in communication. A mixed-method approach was employed, with data collected through focus group discussions involving six participants and documentary analysis of five texts. The study finds out that Kiswahili language variations exist among speakers from different countries. From the focus group discussions and documentary analysis, two broad types of variations were identified: written and spoken. Additionally, semantic variations were observed, such as the use of "bibi" for wife in Tanzania versus "grandmother" in Kenya, the DRC, and Burundi. Other identified variations include phonological differences, contact-induced variations, regional and ethnic variations, and youth languages such as Sheng (Kenya) and Kindubile (DRC). While these variations enrich Kiswahili’s linguistic diversity and reflect sociocultural identities, they may also pose challenges to mutual intelligibility across regions. These findings emphasize the need to address linguistic disparities to enhance Kiswahili’s effectiveness as a global lingua franca.